Electrical Contacts With 2D Materials: Current Developments and Future Prospects. Issue 12 (1st January 2023) - Batool, Saima; Idrees, Muhammad; Han, Su‐Ting; Roy, Vellaisamy A. L.; Zhou, Ye
Abstract: Current electrical contact models are occasionally insufficient at the nanoscale owing to the wide variations in outcomes between 2D mono and multi‐layered and bulk materials that result from their distinctive electrostatics and geometries. Contrarily, devices based on 2D semiconductors present a significant challenge due to the requirement for electrical contact with resistances close to the quantum limit. The next generation of low‐power devices is already hindered by the lack of high‐quality and low‐contact‐resistance contacts on 2D materials. The physics and materials science of electrical contact resistance in 2D materials‐based nanoelectronics, interface configurations, charge injection mechanisms, and numerical modeling of electrical contacts, as well as the most pressing issues that need to be resolved in the field of research and development, will all be covered in this review. Abstract : The physics and materials science of electrical contact resistance in 2D materials‐based nanoelectronics, interface configurations, charge injection mechanisms, and numerical modeling of electrical contacts, as well as the most pressing issues that need to be resolved in the field of research and development, are discussed in this article.